Associations between the Safe Prevention of Primary Cesarean Delivery Care Consensus and Maternal/Neonatal Outcomes - Estrada, Pamela; Tipton, Laura; Chong, Rylan; Towner, Dena; Yamasato, Kelly (American Journal of Perinatology, 2023)
Objective This study aimed to compare cesarean delivery (CD) rates and maternal/neonatal outcomes before and after the 2014 ACOG/SMFM Obstetric Care Consensus for Safe Prevention of Primary CD.Study Design This retrospective study compared unscheduled CD rates and outcomes of singleton, cephalic, term pregnancies at a tertiary-care teaching maternity hospital. Births 5 years before (March 2009–February 2014) and after (June 2014–May 2019) release of the consensus were included. Chi-square and t-test were used to compare outcomes and logistic regression to adjust for confounders.Results In this study, 44,001 pregnancies were included, 20,887 before and 23,114 after the consensus. Unscheduled CD rates increased after the consensus (12.9 vs. 14.3%, p < 0.001); however, there was no difference after adjustment (adjusted odds ratio [aOR], 0.97; 95% confidence interval [CI], 0.91–1.03). Vaginal birth after cesarean (VBAC) deliveries increased among multiparas (4.8 vs. 7.2%, p < 0.001), which remained significant after adjustment (aOR, 1.51; 95% CI, 1.37–1.66). Postpartum hemorrhage, blood transfusion, and chorioamnionitis were modestly increased, while third-degree perineal lacerations decreased. Uterine rupture and neonatal outcomes were unchanged after adjustment.Conclusion At our tertiary-care maternity hospital, the Safe Prevention of Primary CD Care Consensus was not associated with a change in unscheduled CD, though VBAC deliveries increased. We did not demonstrate improved neonatal outcomes and showed increased maternal morbidity that warrants further study.Key Points
Keywords: primary cesarean delivery rate; prevent primary cesarean; pregnancy; vaginal birth after cesarean